Fruit and plantation crop production in the Philippines - Namuco, Leon Ordonez; Protacio, Calixto M. (The University of the Philippines Press, 2010)
This book contains information about fruit and plantation crops commercially grown in the Philippines and the science, technologies and practices behind growing these crops.